Application of cold plasma for performing a typical resection of the spleen; Biomedical Physics and Engineering Express; Vol. 4, iss. 5 - Aleinik A. N. Aleksandr Nikonorovich; Baykov A. N. Aleksandr Nikolaevich; Shevtsova N.; Semichev E. V. Evgeny Vasiljevich; Bushlanov P. S. Pavel Sergeevich; Turgunova N. D. Nataljya Dzhuraboevna (2018, 2018)
Title screen